1023 Examining technostress in nordic region and indian subcontinent. (1st September 2016) - Mubarak, Farooq; Suomi, Reima
Abstract : Background: Despite some academic debates about ICT-induced stress in organisations, the various factors leading to this social phenomenon have not received considerable research attention. Although, differences of opinion still exist, most agree that overtime technostress can induce potentially dangerous psychosomatic sickness that hampers an individual´s personal and professional competence, along with negatively affecting emotions, family, and social relationships. Technostress is a detrimental psychosomatic association between human beings and latest ICT; effects of which can undermine safety and wellbeing in home settings and workplace situations. The theoretical interpretation of ICT-induced stress or technostress is often poorly understood across academic, public, and policy domains. This is mainly due to the fact that technostress is a complex phenomenon involving a range of variables that vary from culture to culture including organisation's own working culture. This paper addresses this literature gap by critically examining the variables responsible for technostress in two distinct world regions: Nordic region and Indian subcontinent. In later sections, the paper discusses the implication of the findings and offers various empowering suggestions to all the players involved in technostress. Methods: Qualitative modes of inquiry including case studies are utilised in this examination to arrive at theoretical constructs, thereby drawing implications for the organisations' board and policy makers alike. The underlying premises hypothesise that the technostress severely affects individuals' wellbeing, social relationships, and offsets their productive competency, particularly at workplace. Results: Evidence indicates growing technostress in Indian subcontinent and Nordic region with increased anxiety, insomnia, psychical and mental strain, depression, and feelings of helplessness. Citizens in Nordic countries are more prone to technostress than their counterparts in Indian subcontinent because the latter suffers from the digital divide and ICT is yet not an integral component of homes and offices. Employees in IT industry often feel compulsive about delivering results in real-time without having enough time to engage in creative and sustained analysis. There are remarkable cultural differences between the two regions that resonate on personal and professional lives. Whereas electronic mails is a preferred medium of communication in Nordic region, traditional paper mail and hand written letters are still widely used throughout the Indian subcontinent with the exception of multinational companies in big cities. Conclusions: The technostress is a synthesis of complex variables working intricately together, and these factors vary in their complexity in two different cultural settings. Technostress is a growing problem which has affected Nordic region tremendously and has started to penetrate Indian subcontinent in big cities. At work places, Information Fatigue Syndrome caused by technostress is hampering concentration and professional competence of employees at a considerable rate. Technostress can be effectively dealt with creating awareness, training on ICT usage in organisations, and usage of ergonomic ICT hardware.